Development of tailored and self-mineralizing citric acid-crosslinked hydrogels for in situ bone regeneration. (November 2015) - Sánchez-Ferrero, Aitor; Mata, Álvaro; Mateos-Timoneda, Miguel A.; Rodríguez-Cabello, José C.; Alonso, Matilde; Planell, Josep; Engel, Elisabeth
Abstract: Bone tissue engineering demands alternatives overcoming the limitations of traditional approaches in the context of a constantly aging global population. In the present study, elastin-like recombinamers hydrogels were produced by means of carbodiimide-catalyzed crosslinking with citric acid, a molecule suggested to be essential for bone nanostructure. By systematically studying the effect of the relative abundance of reactive species on gelation and hydrogel properties such as functional groups content, degradation and structure, we were able to understand and to control the crosslinking reaction to achieve hydrogels mimicking the fibrillary nature of the extracellular matrix. By studying the effect of polymer concentration on scaffold mechanical properties, we were able to produce hydrogels with a stiffness value of 36.13 ± 10.72 kPa, previously suggested to be osteoinductive. Microstructured and mechanically-tailored hydrogels supported the growth of human mesenchymal stem cells and led to higher osteopontin expression in comparison to their non-tailored counterparts. Additionally, tailored hydrogels were able to rapidly self-mineralize in biomimetic conditions, evidencing that citric acid was successfully used both as a crosslinker and a bioactive molecule providing polymers with calcium phosphate nucleation capacity.